Optimization of nano-microsphere flooding and injection-production for tight oil reservoirs based on the three-dimensional physical model - Chen, Fangping; Shen, Zhenzhen; Li, Jian; Yao, Zhenjie; Liu, Kai; Liu, Fangna; Li, Baoting (Frontiers in Earth Science, 2025)
Tight oil reservoirs, such as the Chang 8 formation in the Dadonggou area of the Ordos Basin, commonly encounter severe challenges including strong heterogeneity, and low recovery factors under conventional development methods. Effectively enhancing the recovery of such reservoirs represents a key challenge for efficient field development. Based on the characteristics of the actual reservoir, a large-scale three-dimensional (3D) physical simulation model was designed and constructed. Using two typical horizontal well patterns, row well pattern and five-spot well pattern, physical simulation experiments were conducted to evaluate the effects of N2 flooding, water-alternating-gas (WAG) flooding, water flooding, and nano-microsphere flooding on oil recovery. The results demonstrate that for reservoirs with a permeability of 0.3 mD, WAG flooding significantly improves oil recovery after N2 flooding, increasing the recovery factor by 14.5% and 16% for the row well and five-spot well patterns, respectively. For reservoirs with a permeability of 3.3 mD, nano-microsphere flooding exhibits excellent capability for expanding the sweep volume, resulting in a recovery improvement of 14.5% and 13.5% compared with water flooding for the row well and five-spot well patterns. Additionally, the five-spot well pattern outperforms the row well pattern in terms of recovery efficiency and uniform sweep distribution for all flooding techniques evaluated. This work validated the potential of technologies, such as nano-microsphere flooding, to enhance tight oil recovery, providing key technical support for refined field development.